La formation continue à distance (FAD) des enseignants du secondaire : établissements de l’arrondissement d’Eseka - Njoya Ouzerou Carlos (Multilinguales)
The use of ICTs and the adoption of new teaching / learning and training strategies and techniques, such as the development of distance learning schemes in education systems in Africa in general and Cameroonian in particular, are major challenges for the coming years. Indeed, Sustainable Development Goals (SDGs) defined at the World Leaders’ Conference in September 2015 in New York, the achievement of Objective 3 requires the need for a techno-educational device in order to facilitate the continuous training of teachers regardless of their status (certified, individual or contractual) is needed (B. Charlier, N. Deschryver and D. Peraya, 2006) to make efficient the development of the quality of education. This article proposes to investigate the possibility in Cameroon of continuing education for secondary school teachers through the ADF. This study conducted in four institutions of the district of Eseka located in the department of Nyong and Kellé aims to question, analyze and understand the factors that impede the progress of continuing education through the ADF.